TRANSGENIC NICOTIANA TABACUM PLANTS CARRING RNAi CONSTRUCT RESISTANT TO TWO MOSAIC VIRUSES - Vân, Phạm Thị; Hà, Chu Hoàng; Bình, Lê Trần (Vietnam Journal of Biotechnology, 2011)
Tobacco mosaic virus (TMV) and cucumber mosaic virus (CMV) is one of the most important viral pathogens capable of affecting to many plant species, such as tomato, potato, tobacco, peppe etc. In order to generate fransgenic tobacco plants resistant to both TMV and CMV, RNA interference (RNAi) technology hasbeen applied in this study. A multi-fragment of 625 bp - CPi (including 305 bp from nucleotide 159 - 463 of TMV cp gene and 313 bp from nucleotide 315 - 627 of CMV cp gene) was used to construct a expression vector containing T-CMV-CP RNAi in order to silence the CP gene of both TMV and CMV. This construct was fransformed into tobacco plants (Nicotiana tabacum, cv. K326) via grobacterium tumefaciens. The PCRT-PCR and ELISA analyses indicated that the CPi multi-fragment was stably integrated in tobacco genome and resulted in the absence of TMV and CMV in the inoculated transgenic lines. The resistant valuation of TO fransgenic tobacco plants after three times challenge with TMV and CMV revealed that 34/48 (70.8%) fransgenic lines were completely resistant to both studied vuuses.